Narrative Writing Ability Using Environmental Health Posters among Grade X Students at Senior High School - Moh Sofian Tamran; Juniati; Sukma (Universitas Islam Negeri Palopo, 2026)
Narrative writing is one of the essential competencies in secondary education because it enables students to organize ideas, construct coherent stories, and communicate experiences effectively. Despite its importance, many Indonesian senior high school students continue to encounter difficulties in generating ideas, organizing narrative structures, selecting appropriate vocabulary, and applying correct language conventions. While previous studies have primarily examined the effectiveness of picture media or poster-assisted instruction through experimental or classroom action research designs, limited attention has been given to describing students' narrative writing performance when environmental health posters are employed as contextual visual prompts. This study aimed to describe the narrative writing ability of Grade X students at SMA Negeri 7 Palu using environmental health posters as visual stimuli. Employing a quantitative descriptive research design, the study involved 21 students who completed an individual narrative writing task based on environmental health posters. Students' compositions were assessed using an analytic rubric consisting of four dimensions: content, text organization, language features, and writing conventions. Data were analyzed using descriptive statistics, including individual scores, percentages, class mean, and mastery attainment based on the school's minimum mastery criterion of 75. The findings revealed that students generally demonstrated good narrative writing ability, achieving a mean score of 76.79. Fifteen students (71.43%) achieved the minimum mastery criterion, whereas six students (28.57%) did not. Writing conventions represented the strongest performance area, while language features remained the weakest aspect. These findings indicate that environmental health posters provide meaningful contextual support for generating narrative ideas; however, additional instructional support is still required to strengthen students' vocabulary use, sentence effectiveness, cohesion, and narrative organization. As this study adopted a descriptive design without pre-test, comparison group, or experimental treatment, the findings should be interpreted as a diagnostic profile of students' writing ability rather than evidence of the instructional effectiveness of poster media.